A Life course approach to investigate breast cancer and migration in the greater Paris area: the SENOVIE study protocol - Valéry Ridde; Fanny Chabrol; Emmanuel Bonnet; Annabel Desgrées du Loû; Joseph Larmarange; Anne Gosselin; Annabel Desgrées du Loû; Karna Coulibaly; Hamidou Niangaly; Clémence Schantz; Luis Teixeira; Gaëtan Des Guetz; et al. (BMJ Open)
Introduction Breast cancer is a global public health challenge. It is the most commonly diagnosed cancer and the leading cause of cancer-related death in women. Several inequalities remain among women facing this disease, depending on their country of birth and their sociodemographic characteristics. The SENOVIE study (Therapeutic mobility and breast cancer) aims to understand the life trajectories of women born in France and in sub-Saharan Africa treated for breast cancer in four hospitals in the greater Paris area.Methods and analysis The SENOVIE study is a mixed methods study, combining a quantitative and a qualitative approach. A quantitative retrospective life-event survey is conducted in four hospital centres in the greater Paris area, France, to (1) understand how breast cancer (diagnosis, treatment and possibly reconstruction) impacts the life trajectories of women in many spheres (migration, family life, professional life, financial situation, etc); (2) study the access to healthcare by women living with breast cancer and their determinants; and (3) examine how gender relations may shape breast cancer experience. Women born in France and women born in sub-Saharan Africa are recruited: 1000 women, including 500 per group. In the standardised, face-to-face questionnaire, each dimension of interest is collected year by year from birth until the time of the survey. Clinical and laboratory information is documented with a short medical questionnaire filled out by the medical teams. The qualitative survey is conducted specifically with women born in sub-Saharan Africa who came to France for treatment to better understand their trajectories and the specific obstacles they faced. To analyse the quantitative data collected, descriptive analyses will be used to visualise trajectories (sequence analysis), along with longitudinal analysis methods (survival models and duration models).Ethics and dissemination The study is conducted in accordance with the Declaration of Helsinki. The French Data Protection Authority (Commission Nationale de l’Informatique et des Libertés, declaration number 2231238) and the Committee for Persons’ Protection East I (Comité de Protection des Personnes Est I, national number 2023-A01311-44) approved it. We will disseminate the findings through scientific publications, policy briefs, conferences and workshops.Trial registration number The SENOVIE France study is registered on Clinicaltrial.gov (NCT06503393; registration date: 7 September 2024; https://clinicaltrials.gov/study/NCT06503393).